Spatial Heterogeneity in Tropospheric Column Ozone over the Indian Subcontinent: Long-Term Climatology and Possible Association with Natural and Anthropogenic Activities - Gayatry Kalita; Pradip Kumar Bhuyan (Advances in Meteorology)
Monthly averaged tropospheric ozone residual (TOR) data from TOMS and OMI during the period 1979–2009 are used to study the spatial distribution of tropospheric column ozone within the landmass of the Indian subcontinent, the Tibetan plateau in the north and the Bay of Bengal in the south. The climatological mean shows seasonal maxima in spring and minima in winter in all the regions. The oceanic regions exhibit broad summer maximum and the maximum to minimum ratio is the lowest for these regions. The concentration of tropospheric column ozone is found to be highest in North Eastern India (NE) and the Indo Gangetic plains (IGP). NE ozone concentration exceeds that of IGP during spring whereas in post monsoon and winter reverse is the case. In the monsoon season, O3 levels in the two regions are equal. The spring time highest level of tropospheric column ozone over NE region is found to be associated with highest incidence of lightning and biomass burning activity. The Stratosphere-Troposphere exchange is also found to contribute to the enhanced level of ozone in spring in NE India. A net decrease in tropospheric ozone concentration over NE during the period 1979 to 2009 has been observed.